Insecticidal activity of extracts of plants in the contrl of leaf cutting ant in coffee - Torres, Andrea de Fátima; Lasmar, Olinto; Carvalho, Geraldo Andrade; Santa-Cecília, Lenira Viana Costa; Zanetti, Ronald; de Oliveira, Denilson (Coffee Science - ISSN 1984-3909, 2014)
The objective of this work was to evaluate the efficiency of extracts of plants from Minas Gerais in the control of leaf cutting ant Atta sexdens rubropilosa Forel (Hymenoptera: Formicidae). Seventy plant extracts were evaluated, being applied to the diet of the test insects. It was verified that only the botanical extracts Eugenia florida and Eugenia handroana (Myrtaceae), Trichilia pallida (Meliaceae) and Zanthoxylum pohlianum (Rutaceae) present lethal effect, with mortality average of 16.7; 23.3; 19.7 and 17.3%, respectively.